Sector determination for SVPWM based four‐switch three‐phase VSI - O.C. Kivanc; S.B. Ozturk (Electronics Letters)
Sector determination for a normalised space vector pulse width modulation (SVPWM) scheme is proposed for four‐switch three‐phase (FSTP) voltage source inverter (VSI) by using already available stationary reference frame stator voltages without requiring complex trigonometric calculations. The proposed method has been simulated by using MATLAB/Simulink and implemented using a VSI with a TMS320F28335 floating‐point digital signal processing. Simulation and experimental results show the feasibility and effectiveness of the proposed SVPWM algorithm for FSTP inverter.